Foot reflexology in painful conditions: systematic review - Artioli,Dérrick Patrick (2021)
ABSTRACT BACKGROUND AND OBJECTIVES: Because foot reflexology is commonly associated with other interventions, its benefits are difficult to establish. In addition, systematic reviews have been carried out many years ago, analyzing unspecific parameters and with controversial results. Thus, the objectives of this study were: to analyze the results of randomized controlled trials with a control group in painful conditions, using foot reflexology as a single intervention; describe the proposed application and methodological quality of the studies (PEDro scale). CONTENTS: The PEDro, Pubmed, Scielo and LILACS data bases were consulted, searching for clinical trials with the following keywords and Boolean index: Foot Reflexology AND pain; reflexology foot massage AND pain (English, Portuguese and Spanish). These keywords should have been present in the title or summary of the article for inclusion, directing to pain and moving away from other variables. 95 studies were found, 17 were selected and most of the results were favorable. The usual application varies from 2-30 minutes of stimulation on each foot, varying between massaging in general or using the somatotopic map stimulating the solar plexus, pain correspondence zone and accessory points related to the diagnosis. In short, the studies showed moderate to good methodological quality according to the PEDro scale. CONCLUSION: Foot reflexology has shown promise for pain relief as an isolated therapy in neuromusculoskeletal cases in hospital and outpatient settings. The hope is that studies of excellent methodological quality can support this statement in the near future.